Integrated coastal management strategies to enhance biodiversity conservation in Karimunjawa National Park, Jepara, Central Java, Indonesia - SURYANTI SURYANTI; MAX RUDOLF MUSKANANFOLA; SIGIT FEBRIANTO; CHURUN A’IN (Society for Indonesian Biodiversity, 2025)
Abstract. Suryanti S, Muskananfola MR, Febrianto S, A’in C. 2025. Integrated coastal management strategies to enhance biodiversity conservation in Karimunjawa National Park, Jepara, Central Java, Indonesia. Biodiversitas 26: 3011-3020. The Karimunjawa National Park area in Jepara, Central Java, Indonesia, boasts various coastal resources and ecosystems, including mangroves, seagrasses, and coral reefs, which serve as habitats for several important organisms. Therefore, a coastal area management strategy is needed to maintain the sustainability of coastal resources. This study focuses on efforts to preserve and conserve biodiversity, especially protected biota in the Karimunjawa National Park area. This research was conducted on three islands representing each ecosystem: Kemujan Island for the mangrove area, Cemara Kecil Island for the seagrass area, and Menjangan Besar Island for the coral reef area. The research method used is quantitative descriptive. The primary data used in this study comprise biota inventory data and environmental parameters collected from each island, representing each ecosystem. Data analysis employs a community structure formula to calculate uniformity, diversity, and dominance indices, as well as a SWOT analysis to inform management strategies. The results show that the diversity index (H') is moderate, the uniformity index (e) is relatively stable, and the dominance index (C) does not contain a dominant species. Environmental parameters are also still suitable for the life of biota associated with the ecosystem. The coastal management strategies that can be implemented in Karimunjawa National Park are in quadrant 1. These strategies capitalize on the area's existing strengths and leverage its opportunities.